On a snow cover composition in the vicinity of the Verkhnekamsky Salt Deposit - S. M. Blinov; E. A. Menshikova; E. N. Baturin; E. S. Ushakova; L. R. Zolotarev (Лëд и снег, 2015)
The snow cover chemical composition was investigated on the territory of the Verkhnekamskiy potash-magnesium salt deposit in the zone of influence of atmospheric emissions of Berezniki Potash Mining Complex (Perm Region). The object of researches was the snow in this area. Features of specific pollutants contained in the emissions of these mine groups and their relationship with the air intake and following atmospheric deposition were examined. With regard for specific character of pollutants in the emissions, studies of melt water included determination of the following chemical components – SO42-, Cl-, NO3-, NO2-, НCO3-, Ca2+, Mg2+, Na+, K+, of the pH value as well as suspended solid substances, and total mineralization. An analysis of snow composition was performed on two sites from which one was the surrounding background territory, while another area was the urban territory of city Berezniki, i.e. area of operating mine group. To assess the results the indicator of specific stock macro component was used. Increased specific stock relative to the background snowpack is clearly indicative of components directly related to the extraction and processing of salts Cl-, Na+, K+. The revealed anomalies have a local character and, as a rule, do not extend beyond boundaries of sanitary protection zones of the enterprises. Maps of distribution of values of the specific reserves for the analyzed list of components in the melt water were constructed. Our results obtained for the Verkhnekamskiy Deposit area were compared with similar published data on the territories of cities in the zone influenced by motor roads, reserves, and coastal zones of the Russian Arctic seas.